The Influence of Principal Leadership and Work Motivation on Teacher Work Discipline - Sahadi Sahadi; Yasir Arafat; Tri Widayatsih (research, training and philanthropy institution Natural Aceh, 2021)
This study aims to determine the effect of principal leadership and work motivation on teacher work discipline. As for the formulation of the problem: (1) is there an influence between the principal's leadership on teacher work discipline?, (2) is there an influence between work motivation on teacher work discipline?, (3) is there a significant influence between principal leadership and work motivation jointly on teacher work discipline?. This research uses descriptive analysis method. The method used by researchers to get a view of the principal's leadership, work motivation and teacher work discipline. The sample in this study amounted to 108 teachers. From the results of the descriptive statistical analysis of the principal's leadership, the very good data category was chosen by 8 out of 108 (9.6%) respondents. While the good category was chosen by 21 respondents (25.3%). The sufficient category was chosen by 30 respondents (36.1%). 19 (23.0%) respondents chose the less category. For the very less category chosen by 5 (6.0%) respondents. If it is related to the mean value on the discipline questionnaire, which is 74.4819, then the average respondent chooses the sufficient category.